Efisiensi Penggunaan Air Irigasi pada Saluran Sekunder di Daerah Irigasi Tungkub - Mentari Kinasih; Ni Nyoman Sulastri; I Wayan Tika; Sumiyati Sumiyati; Ida Ayu Gede Bintang Madrini; Made Darmayasa (Jurnal BETA (Biosistem dan Teknik Pertanian), 2023)
Good distribution of irrigation water will produce abundant harvests. It will improve the welfare of farmers. The efficiency of water utilization is important in irrigation schemes because it determines the performance of the irrigation network. This research aims to obtain the efficiency of irrigation water in DI Tungkub in secondary channels. This research took direct debit data at 11 points in the secondary channel. Climate data was obtained from NASA POWER and BMKG Region III Denpasar. Rainfall data was obtained from 3 rain stations (Tibubeneng, Kapal, and Mengwi Gede). The area of rice fields observed was 416 Ha (Upstream), 349 Ha (Central), and 164 Ha (Downstream). The research results show that Zone A has the highest usage efficiency level of 68% which occurred in May I and the lowest 14.1% in March I. Zone B has the highest usage efficiency of 100% (occurring in the periods April I, April II, June II, and July I), and the lowest was 0% in the May I and May II periods. Zone C had the highest usage efficiency of 100% which occurred in June I and June II, while the lowest usage efficiency occurred in March I at 35%..